DISKREPANSI KOMPETENSI PROGRAM STUDI DAN DUNIA KERJA: PERSPEKTIF LULUSAN PROGRAM STUDI PENDIDIKAN DAN PENGAJARAN AGAMA KATOLIK - Mukarramah, Mukarramah; Martinus, Martinus; Pongkot, Herkulanus (Bahasa Indonesia, 2023)
The background of this research is the occurrence of discrepancies or gaps between the competencies expected by the study program and the reality experienced by graduates of the Catholic Religious Education and Teaching study program in the world of work. This study aims to find out what gaps occur in graduates in facing the world of work and propose solutions that can be considered to minimize these discrepancies. The research method used is descriptive quantitative with survey techniques and Focus Group Discussion (FGD). The results found are that there are discrepancies in the aspect of alumni's mastery of English, ability to work under pressure, and ability to fulfill administrative tasks. Based on the results, it can be concluded that discrepancies or gaps that occur can be overcome by holding English days and mentoring, spiritual strengthening, and curriculum development sustainably.